2015
DOI: 10.3390/ijgi4031605
|View full text |Cite
|
Sign up to set email alerts
|

Movement Pattern Analysis Based on Sequence Signatures

Abstract: Increased affordability and deployment of advanced tracking technologies have led researchers from various domains to analyze the resulting spatio-temporal movement data sets for the purpose of knowledge discovery. Two different approaches can be considered in the analysis of moving objects: quantitative analysis and qualitative analysis. This research focuses on the latter and uses the qualitative trajectory calculus (QTC), a type of calculus that represents qualitative data on moving point objects (MPOs), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Their technique initially determines the simplified dense trajectories of a single object and then converts these trajectories into 2D images. Chavoshi et al [5] presented a visualization technique, sequence signature (SESI), to convert a basic variation of QTC (QT C B ) movement patterns of moving point objects into a 2D indexed rasterized matrix. The approach in [12] represents trajectories of pair-vehicles as a series of heat sources, where a thermal diffusion process creates an activity map as a 2D matrix.…”
Section: Trajectory Analysis Techniquesmentioning
confidence: 99%
“…Their technique initially determines the simplified dense trajectories of a single object and then converts these trajectories into 2D images. Chavoshi et al [5] presented a visualization technique, sequence signature (SESI), to convert a basic variation of QTC (QT C B ) movement patterns of moving point objects into a 2D indexed rasterized matrix. The approach in [12] represents trajectories of pair-vehicles as a series of heat sources, where a thermal diffusion process creates an activity map as a 2D matrix.…”
Section: Trajectory Analysis Techniquesmentioning
confidence: 99%
“…The method first extracts the simplified dense trajectories of single object and then converts these trajectories into 2D images. Chavoshi et al (Chavoshi et al, 2015) proposed a visualization technique, sequence signature (SESI), to transform the simplest variant of QTC (QTC B ) movement patterns of moving point objects (MPOs) into a 2D indexed rasterized space. The method in (Lin et al, 2013) represents trajectories of pair-vehicles as a series of heat sources; then, a thermal diffusion process creates an activity map (or 2D matrix).…”
Section: Related Workmentioning
confidence: 99%
“…It could be advantageous to facilitate the application of MPA to explore methods for integrating automated methods that might be implemented without eliminating the essential expert perspective; such efforts could, for example, permit either more rapid coding of an MPA interview along with facilitating broader application to larger numbers of individuals. While we posit that the complexity of detecting PGMs—highly integrated movement patterns that require perception of the whole body in motion—will prove to be a substantial challenge for developers of automated coding systems, there are studies which have shown initial levels of success at representing the body movements of a samba dancer (Chavoshi et al, 2015 ), along with application of LMA to detect hand movements (Lourens et al, 2010 ) and segmentation of a repertoire of motions (Bouchard and Badler, 2007 ).…”
Section: Future Directionsmentioning
confidence: 99%